Spatial transcriptomics reveals macrophage domestication by epithelial cells promotes immunotherapy resistance in small cell lung cancer - Yu Sun; Minghui Zhang; Yanbin Zhao; Yubo Yan; Lei Wang; Xuhui Liu; Songsong Xia; Bingbing Wang; Xiaoxin Zhang; Yan Wang (npj Precision Oncology)
Abstract Small cell lung cancer (SCLC) remains a lethal malignancy. Although immunochemotherapy regimens have improved patient survival rates, drug resistance still occurs in a significant subset of patients, highlighting the importance of elucidating the mechanisms within the tumor microenvironment. Here, we applied spatial single-cell transcriptomics to investigate the spatial characteristics of SCLC and their associations with immunochemotherapy resistance. By analyzing samples from 18 patients with extensive-stage SCLC, we identified two distinct epithelial cell subtypes: Epi-I and Epi-II. Epi-I exhibited high proliferative activity and was associated with treatment resistance and poor survival outcomes. In contrast, Epi-II showed more spatial contact with immune cells and was associated with treatment sensitivity. Further analysis uncovered a fascinating cellular transition paradigm, wherein Epi-I may be derived from Epi-II, with myeloid cells playing a facilitatory role in this transformation cascade. Specifically, within the spatial zone that was enriched with the Epi-II, epithelial cells may secrete MIF gene, which promoted the polarization of myeloid cells towards the M2 macrophages. The M2-polarized myeloid cells subsequently upregulated the expression of SPP1 that in turn triggered the activation of the PI3K-AKT signaling pathway in the adjacent epithelial cells, driving the conversion of Epi-II to Epi-I cells. Our findings revealed that the intricate crosstalk between epithelial and myeloid cells constitutes a pivotal resistance mechanism in SCLC, and targeting the SPP1/MIF pathway emerged as a promising strategy with the potential to enhance the treatment efficacy.